- g_assert_cmpstr(udnp1->dict1.string1, ==, udnp2->dict1.string1);
- g_assert_cmpint(udnp1->dict1.dict2.userdef1->integer, ==,
- udnp2->dict1.dict2.userdef1->integer);
- g_assert_cmpstr(udnp1->dict1.dict2.userdef1->string, ==,
- udnp2->dict1.dict2.userdef1->string);
- g_assert_cmpstr(udnp1->dict1.dict2.string2, ==, udnp2->dict1.dict2.string2);
- g_assert(udnp1->dict1.has_dict3 == udnp2->dict1.has_dict3);
- g_assert_cmpint(udnp1->dict1.dict3.userdef2->integer, ==,
- udnp2->dict1.dict3.userdef2->integer);
- g_assert_cmpstr(udnp1->dict1.dict3.userdef2->string, ==,
- udnp2->dict1.dict3.userdef2->string);
- g_assert_cmpstr(udnp1->dict1.dict3.string3, ==, udnp2->dict1.dict3.string3);
+ g_assert_cmpstr(udnp1->dict1->string1, ==, udnp2->dict1->string1);
+ g_assert_cmpint(udnp1->dict1->dict2->userdef->integer, ==,
+ udnp2->dict1->dict2->userdef->integer);
+ g_assert_cmpstr(udnp1->dict1->dict2->userdef->string, ==,
+ udnp2->dict1->dict2->userdef->string);
+ g_assert_cmpstr(udnp1->dict1->dict2->string, ==,
+ udnp2->dict1->dict2->string);
+ g_assert(udnp1->dict1->has_dict3 == udnp2->dict1->has_dict3);
+ g_assert_cmpint(udnp1->dict1->dict3->userdef->integer, ==,
+ udnp2->dict1->dict3->userdef->integer);
+ g_assert_cmpstr(udnp1->dict1->dict3->userdef->string, ==,
+ udnp2->dict1->dict3->userdef->string);
+ g_assert_cmpstr(udnp1->dict1->dict3->string, ==,
+ udnp2->dict1->dict3->string);